Implementation of an educational program to improve precepting skills. Issue 4 (5th April 2021) - Fincham, Sarah J.; Smith, Todd; Purath, Janet
ABSTRACT: Background: Educating health care providers is dependent on developing high-quality clinical preceptors, yet preceptors face widespread challenges to precepting, such as time constraints and lack of formal preceptor training. Local problem: Our college of nursing conducted a needs assessment survey of our preceptors to better understand the barriers to and incentives for precepting. Formal preceptor training was identified as an intervention to support preceptors. Methods: Based on survey responses and a literature review of best practices, a preceptor training program was developed and delivered to local health care partners. Posttraining surveys were used to measure the effectiveness of the training. Intervention: We developed a one-hour formal preceptor training program. The main components included 1) orienting a student, 2) applying the Recorder/Reporter-Interpreter-Manager-Educator (RIME) framework for clinical evaluation, 3) One-Minute Preceptor (OMP) methodology for clinical teaching, 4) strategies for giving students feedback, and 5) communicating with the university. Results: Preceptor training was delivered to health care providers (N = 58) at eight clinics and one nurse practitioner (NP) professional group. Most participants (86%) had never received training in the RIME framework or OMP method (80%). The participants rated the following aspects of training as very useful or moderately useful: Orientation checklist (100%), RIME framework (96%), and OMP (100%). Conclusions: We found that training preceptors on evidence-based, time-efficient strategies for precepting is feasible and valuable. If continued and expanded, this training may positively affect retention and recruitment of preceptors for our university's NP students. This training may be transferable to other geographical settings.